Analysis of Digital Literacy Technology Design for the Department of Mechanical Engineering Based on a Website at Universitas Muhammadiyah Sumatera Barat - Desmarita Leni; Muchlisinalahuddi Muchlisinalahuddi; Riza Muharni; Arwizet K (Universitas Negeri Padang, 2023)
This research aims to analyze the level of importance of digital literacy understanding among students of Mechanical Engineering at the University of Muhammadiyah (UM) Sumatera Barat. The digital literacy developed in this study not only facilitates access to learning references, literature, research methodologies, and testing in the field of Mechanical Engineering but also designed as a data storage place for student practical and research testing results. This research used a questionnaire as a data collection technique, which was filled out by Mechanical Engineering students at Universitas Muhammadiyah Sumatera Barat. The first questionnaire was conducted to measure the level of students' understanding of digital literacy in the field of Mechanical Engineering, and the results were used as the basis for creating a literacy website. The second questionnaire was conducted to evaluate the created literacy website. Data analysis was performed using quantitative descriptive analysis. The results showed that 57% of respondents had good understanding of digital literacy in the field of Mechanical Engineering. However, only 15% of respondents often searched for references on digital technology, and 80% of respondents faced difficulties in finding credible digital literacy sources. Moreover, most respondents expressed their interest in learning and using digital technology in research and practical work. These results served as the basis for creating a digital literacy website. The digital literacy website was evaluated, and the evaluation result showed that most respondents stated that the created literacy website was easy to use and helpful in the learning or task completion process. However, some aspects needed improvement, such as relevant and understandable content and the quality of content presentation that is more interesting for respondents. Overall, the literacy website has a high level of satisfaction in several aspects.